Aplicando a técnica de simulação hardware-in-the-loop no desenvolvimento de um simulador híbrido para testbeds de redes de sensores sem fio - Brito Filho, Elio Ribeiro de (2014)
This paper presents an alternative to scale testbeds for wireless sensor networks. The approach in this research was based on the recurrence of Hardware-In-the-Loop simulation technique to co-relate real sensor nodes with virtual sensor nodes. A literature review of explanatory feature enabled the fundamentals of this research and allowed the definition of predicates for targeting a functional solution. The design of the approach used was materialized through the implementation of a scalable and high-fidelity hybrid simulator. A series of tests/benchmarks took effect in order to legitimate the current study, that allowed us to evaluate the integrity, operating cost and limitations present in the infrastructure. The applied assessment confirmed the compliance of the outlined goals and the identification of some limitations related to the hardware.